Upending the norms: the representation of Theyyam in Kerala’s popular culture - Saranya Jayaprakash A.; Senguttuvan M. (Cogent Arts & Humanities, 2024)
Theyyam is an old socio-religious ritual from North Kerala that has been practised in different parts of Malabar for a very long time, particularly by certain castes or tribes such as Malaya, Pulaya, Thiyya, Vannan, etc. It is a type of worship in which a common man assumes the role of a god and engages in a ritualistic dance and the performance is meant to benefit the society by bringing wealth and prosperity. Theyyam has experienced many transformations and been incorporated into the social order. This article uses a few chosen materials that include Malayalam short films and album tracks (Neeli, Varav, Kaavakam, and Pambichi) which portray the traditional folk form Theyyam. The convergence of gender performativity and counter-hegemony in the portrayal of Theyyam as a traditional folk art is the focus of this research article. This study examines how social power dynamics, gender issues, and caste conflict are interwoven with Theyyam through an analysis of the selected discourses. It demonstrates the ways in which alternate gender role presentations have been a part of subaltern opposition to dominant caste authority through the employment of Theyyam. The paper also explores how popular culture absorbed and exalted the powerful Theyyam, revealing the intricacies of its portrayal and possibly exposing societal hypocrisies.